Hemodialysis Effect on Systolic Left Ventricular Function in Stage V Chronic Kidney Disease Patients - Hazbina Fauqi Ramadhan; Yuli Hermansyah; Desie Dwi Wisudanti; Suryono Suryono (Faculty of Medicine, University of Jember, 2018)
Chronic kidney diasease (CKD) is one of world health problem with increased incidence. Kidney function impairment contribute to cardiovascular complication that has been the main cause of CKD patient death. The impairment of cardiovascular function mainly caused by decreased of systolic left ventricular function. Stage V CKD patients need renal replacement therapy such as hemodialysis. Hemodialysis known to has positive effect on cadiovascular function by decreasing volume overload and uremic toxin. Echocardiography is a non-invasive method to assess cardiovascular function i.e. systolic left ventricular function. The aim of this study is to describe the improvement of systolic left ventricular function in stage V CKD patients after going through hemodialysis. The subject of this study are 30 patients, ≥18 years old diagnosed with Stage V CKD and undergo routine hemodialysis in RSD dr. Soebandi Jember. The data analyzed with Wilcoxon test and shown significance (p=0,000). This study concludes there is a significant improvement on systolic left ventricular function in CKD patients before and after hemodialysis in RSD dr. Soebandi Jember. Keywords: Systolic Left Ventricular Function, Hemodialysis, Chronic Kidney Disease, Echocardiography